Analisis Potensi Pengembangan Komoditas Unggulan Udang Vaname (Litopenaeus vannamei) di Kabupaten Bengkalis, Provinsi Riau: - - Riza, Subkhan; Gapar; Setyawati, Rafika (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2025)
The coastal area of Bengkalis Regency is extensive and holds significant potential for aquaculture development; however, much of this potential remains underutilized. The purpose of this research is to: 1) determine the existing condition of potential aquaculture resources, 2) analyze the fisheries sector's contribution to the economy, and 3) identify location-specific superior aquaculture commodities in Bengkalis Regency. This research employed a literature study method. Results indicate that out of 27,775.79 Ha of potential aquaculture land, only 233.22 Ha (8.40%) has been utilized. Specifically for shrimp ponds, only 129.03 Ha (9.06%) of the 1,423.89 Ha potential is in use. Although the fisheries sector's contribution to the Gross Regional Domestic Product (GRDP) from 2019 to 2023 remains relatively small (3.05%–6.22%), the Location Quotient (LQ) value (>1) indicates that fisheries is a base sector in Bengkalis Regency. Furthermore, agglomeration and specialization analyseswith an αit value of ∞ 1, it indicates that aquaculture is concentrated and is a specialized business activity.. The specific superior commodity identified is Vannamei shrimp (Litopenaeus vannamei), which is widely cultivated using intensive technology, efficient production facilities, and feed management..